Respuesta :

Answer:

x = -6

y = -6

Step-by-step explanation:

Solve using substitution.

Substitute 2x + 6 for y:

4x - 4(2x + 6)=0

Distribute the 4 to each term in the parentheses:

4x - 4(2x) - 4(6) = 0

4x - 8x - 24 = 0

Combine like terms

-4x - 24 = 0

Add 24 to both sides

-4x = 24

Divide both sides by -4

x = -6

Plug -6 back in for x to solve for y:

y = 2x + 6 = 2(-6) + 6 = -12 + 6 = -6

(x, y) = (-6, -6)

Answer:

x= -6 and y= -6

Step-by-step explanation:

Take 4x-4y=0 as eqn 1

and y=2x+6 as eqn 2

Substitute eqn 2 into eqn 1

4x -4(2x+6)=0

4x-8x-24=0

-4x-24=0

Move -24 to the other side

-4x=24

Divide both sides by -4

[tex] \frac{ - 4x}{ - 4} = \frac{24}{ - 4} [/tex]

x= -6

substitute x= -6 in eqn 2

y=2(-6)+6

y= -12+6

y= -6

ACCESS MORE